Registration of BARBREN‐713 Germplasm Line of Upland Cotton Resistant to Reniform and Root‐Knot Nematodes. Issue 1 (16th December 2014) - Bell, Alois A.; Robinson, A. Forest; Quintana, Jose; Duke, Sara E.; Starr, James L.; Stelly, David M.; Zheng, Xiuting; Prom, Sandria; Saladino, Vince; Gutiérrez, Osman A.; Stetina, Salliana R.; Nichols, Robert L.
Abstract : Cotton ( Gossypium hirsutum L.) germplasm line BARBREN‐713 (Reg. No. GP‐987, PI 671965) was developed and released by the USDA–ARS, Mississippi Agricultural and Forestry Experiment Station, Texas A&M AgriLife Research, and Cotton Incorporated in 2012. The objective of the release was to provide public and private breeders with an agronomically desirable germplasm that is resistant to both the reniform nematode ( Rotylenchulus reniformis Linford and Oliveira) and the root‐knot nematode [ Meloidogyne incognita (Kofoid and White) Chitwood]. The line also has excellent seedling vigor in fields infested with nematodes and fungal root rot pathogens, such as Thielaviopsis basicola, Rhizoctonia solani and Fusarium spp. Resistance to reniform nematode was transferred from G. barbadense GB713 (PI 608139) and is associated primarily with the Ren 2 GB713 gene on chromosome 21. Resistance to root‐knot nematode was transferred from the germplasm line M‐315 RNR (PI 592514), 'LA 887', or 'Acala Nem‐X' and is associated primarily with the Mi‐1 gene on chromosome 11. The codominant simple sequence repeat markers, BNL 3279_105 and CIR 316_202, respectively, were closely linked to the resistance genes. A single nucleotide polymorphism marker, Gl‐187401, also was developed to detect the Ren 2 GB713 gene. In controlled environment assays, BARBREN‐713 suppressed reproduction of both nematodes by 90% or more. It also reduced reniform nematode populations in the field at eight locations in four states. The line has fiber quality similar to M‐315 RNR but yielded more than M‐315 RNR in reniform nematode‐infested fields.